The labour competitions as a variable linked to organizational learning in teachers - Torres Valladares, Manuel (2012)
The purpose of the present study is analyzing the relations that could exist between the labour competitions and the organizational learning in teachers from Comas’ public educational institutions. A sample of 240 teachers was taken and two evaluations instruments were applied, one for each variable. The results show that significant and positives correlations exist between the variables of study, furthermore it was found that women teachers have better results in the organizational learning than men teachers.